Delphi survey to identify topics to be addressed at the initial follow‐up consultation after oesophageal cancer surgery. Issue 13 (15th October 2014) - Jacobs, M.; Henselmans, I.; Macefield, R. C.; Blencowe, N. S.; Smets, E. M. A.; de Haes, J. C. J. M.; Sprangers, M. A. G.; Blazeby, J. M.; van Berge Henegouwen, M. I.
<x xml:space="preserve">Abstract</x> Background There is no consensus among patients and healthcare professionals (HCPs) on the topics that need to be addressed after oesophageal cancer surgery. The aim of this study was to identify these topics, using a two‐round Delphi survey. Methods In round 1, patients and HCPs (surgeons, dieticians, nurses) were invited to rate the importance of 49 topics. The proportion of panellists that considered a topic to be of low, moderate or high importance was then calculated for each of these two groups. Based on these proportions and the i.q.r., topics were categorized as: 'consensus to be included', 'consensus to be excluded' and 'no consensus'. Only topics in the first category were included in the second round. In round 2, panellists were provided with individual and group feedback. To be included in the final list, topics had to meet criteria for consensus and stability. Results There were 108 patients and 77 HCPs in the round 2 analyses. In general, patients and HCPs considered the same topics important. The final list included 23 topics and revealed that it was most important to address: cancer removed/lymph nodes, the new oesophagus, eating and drinking, surgery, alarming new complaints and the recovery period. Conclusion The study provides surgeons with a list of topics selected by patients and HCPs that may be addressed systematically at the initial follow‐up consultation after oesophageal cancer surgery.